Influence of network density on information diffusion on social network sites: The mediating effects of transmitter activity. (June 2016) - Luarn, Pin; Chiu, Yu-Ping
Information diffusion through social network sites is a new and important context that has received scant attention in extant research. This study developed a Facebook application to uncover the influence of network density and transmitter activity on the information diffusion process. The results showed that network density is positively related to transmitter activity on social network sites. In addition, transmitter activity partially mediated the effect of network density on the extent of information viewed and retransmitted. That is, transmitter activity can affect the information diffusion process, and the activity effect is plausible and should become stronger as social networks become denser. The findings of this study provide useful implications, not only for theory in the social network, but also useful references and suggestions to marketing practitioners.